Tiling optimization in numerically solving a multidimensional heat equation on a ring of processors - Sobolevsky, P. I.; Bakhanovich, S. V.; Gorbach, A. N. (Cybernetics and systems analysis, 2010)
The problem of tiling optimization in solving the first boundary problem for a multidimensional heat equation on supercomputers with distributed memory is investigated. Estimates of amounts of computations and communications are obtained. Tiling optimization is reduced to the minimization of the execution time of an algorithm as a function of the tile size, computing environment size, processor throughput, and latency and bandwidth of communication channels.